PENGEMBANGAN DAN EVALUASI EFEKTIFITAS SISTEM INFORMASI ADMINISTRASI DAN MANAJEMEN PAUD BERBASIS WEB MELALUI PENERAPAN MODEL ADDIE DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN - Farhani, Deswita; Nurhaliza; Az Zahrah, Fathanah; Dwi Salsabilah, Salwa; Rianti, Milda; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and evaluate the effectiveness of a web-based early childhood education (PAUD) administration and management information system through the application of the ADDIE model in improving the quality of educational services. This study uses the Research and Development (R&D) method with stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects include school principals, teachers, administrative staff, and parents of students. Data collection techniques are conducted through observation, interviews, questionnaires, and documentation. The study results indicate that the web-based PAUD administration and management information system has the potential to be a feasible and effective medium in supporting administrative management, data processing, and information delivery in PAUD institutions. The implementation of this system also contributes to improving work efficiency and the quality of educational services. Thus, a web-based information system through the ADDIE model can become a solution in supporting.